ЧАСТОТНО-ФАЗОВЫЕ ЛАЗЕРНЫЕ ИЗМЕРИТЕЛИ ПЕРЕМЕЩЕНИЙ И ВИБРАЦИЙ С ОПТИЧЕСКОЙ КАЛИБРОВКОЙ - Брагинец, И.А.; Зайцев, Е.А.; Кононенко, А.Г.; Масюренко, Ю.А.; Ниженский, А.Д. (Інститут електродинаміки НАН України, Київ, 2011)
The structural diagram of the single-channel laser frequency-phase rangefinder system that can be used to determine linear displacement and vibration parameters has been considered. Feature of the device is the introduction of its algorithm mode optical calibration, designed to reduce the influence of phase distortions that occur in high frequency circuits, as well as the instability characteristics of electronic measuring units. Emerging with additional measurement errors has been evaluated and methods to reduce them have been suggested. A comparative evaluation of phase and frequency phase meters of displacement has been evaluated. It is noted that the resolution of the frequency-phase systems with some increase of their hardware expenditures is higher than that of phase systems. References 6, figures 2.